APPEARANCE AND EVOLUTION OF MARINE BENTHIC COMMUNITIES IN THE EARLY PALAEOZOIC - Rozhnov S.V. (My University, 2006)
The development of marine benthic communities in the Early Palaeozoic occurred mainly in the shallow water epicontinental seas. It included those stages of the Cambrian and Ordovician evolutionary radiations that were dominated by a high rate of morphogenesis, when new food and territory resources were not limited. This provided many opportunities for coadaptation of emerging organisms. At the time of the Cambrian radiation, the body plans of all animals were formed, while in the Ordovician, the maximum rank of emerging taxa did not exceed the level of class. The beginning of each radiation was explosive. Vendian benthic communities developed in cold seas and in the shallowest areas of warm seas, where organic matter from the surface layers was available at the bottom because of the absence of a thermocline. The Cambrian radiation began with the appearance of pelagic suspension feeders, because of which much of the primary production could penetrate the thermocline and settle at the bottom.